1986
DOI: 10.1103/physrevlett.57.1378
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Spectral and Dynamical Properties of Two-Level Systems

Abstract: In a very interesting recent Letter,^ several statistical properties of the energy levels of a single two-level atom interacting with one quantized electromagnetic mode were investigated, and it was found that the nearest-level spacing was highly correlated and regular, in contrast to chaotic dynamical behavior found in a semiclassical version of this model (for references see Ref. 1). Similar regularities in the same system had also been found by Graham and Hohnerbach^ and Graham,^ but for sufficiently strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 3 publications
1
52
0
Order By: Relevance
“…In accordance with the results of [5] and [6], we find that the individual semi-classical trajectories can exhibit chaos for specific values of the system parameters. Using the method of Benettin et al [18], we evaluate the Lyapunov coefficient X which in the case of Fig.…”
Section: S=-tv Spin [Ejn Es ]supporting
confidence: 74%
See 1 more Smart Citation
“…In accordance with the results of [5] and [6], we find that the individual semi-classical trajectories can exhibit chaos for specific values of the system parameters. Using the method of Benettin et al [18], we evaluate the Lyapunov coefficient X which in the case of Fig.…”
Section: S=-tv Spin [Ejn Es ]supporting
confidence: 74%
“…and similar relations connect the coordinates q and momentum p to the corresponding quantum operators q and p. The operator S£ c{ is identical to the Liouvillian of a classical dipole interacting with a classical oscillator, i.e., this term alone corresponds to the semi-classical set of equations discussed by various authors [5,6]. We refer to the calculations based on the study of the single trajectory solutions of the nonlinear dynamic equations as the semiclassical predictions.…”
Section: Extended Wigner Formalismmentioning
confidence: 99%
“…The level statistics for finite N have revealed the existence of quantum chaos in certain isolated regimes of the model [11,12]. On the other hand, the QPT aspect for N → ∞ has been discussed in the context of superradiance [13,14], and recently for exciton condensation [15].…”
mentioning
confidence: 99%
“…For example, the entanglement and the QPT in the rotating-wave approximation (RWA) is reported in [6], which suggests that the entanglement only occurs in the strong coupling limit. The model has also been extensively studied without the RWA, with its quantum-chaotic properties discussed by several other authors [12][13][14][15], without reference to the QPT.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many aspects of the model have been studied, such as the dynamical properties of quantum entanglement and decoherence [3][4][5][6][7][8], quantum phase transitions (QPT) [2,[9][10][11] and chaotic properties [3,5,9,10,[12][13][14][15]. Furuya et al [3] did the initial work on the entanglement process in a varied version of the model and concluded that for short times, there is a faster increase in decoherence for chaotic initial conditions as compared to regular ones, which have an oscillatory increase.…”
Section: Introductionmentioning
confidence: 99%